Sociodemographic factors influencing smartphone addiction in university students - Inmaculada Aznar-Díaz; Juan-Manuel Trujillo-Torres; Santiago Alonso-García; Carmen Rodríguez-Jiménez (Research in Social Sciences and Technology- OpenED Network, 2019)
The development of mobile devices has affected the way of life of university students, affecting their daily habits and sometimes their health. Specifically, in recent years a series of illnesses have developed as a result of the constant use of smartphones by the university population, which has come to be catalogued as an at-risk population. The aim of this work was to analyze the sociodemographic factors that influence the smartphone addiction of university students. For the measurement of the levels of addiction, the standardized instrument Smartphone Addiction Scale was used in a sample of 385 students from the University of Granada, Spain. A multiple linear regression model was used as a statistical test, highlighting that the factor influencing smartphone addiction is the time of use. Finally, the study includes a series of implications derived from the results obtained, with the aim of establishing preventive measures to help to mitigate smartphone addiction.